(untitled) (KULT_online, 2010)
This collection of essays edited by U.S. historians Robbie Lieberman and Clarence Lang is an important contribution to the growing field of ‘revisionist’ historiography, which deals with 1950s U.S. culture and a renewed understanding of the early Cold War, anticommunism and its relation to the African American fight for racial progress. The six essays focusing on little-known aspects of 1950s black radical activism argue for the destructive impact which McCarthyism had on the African American movement for racial equality. They thereby ultimately challenge and complicate the historiographical notion that the Cold War was beneficial to the success of the black freedom movement.